Harvesting effects on functional structure and composition of tropical invertebrate assemblages. (8th October 2015) - Jimenez, Haizea; Dumas, Pascal; Mouillot, David; Bigot, Lionel; Ferraris, Jocelyne
Abstract: Anthropogenic disturbances affect ecosystem structure and functioning. The quantification of their impacts on highly diverse and structurally complex ecosystems, such as coral reefs, is challenging. These communities are facing rising fishing pressure, particularly on Pacific Islands such as New Caledonia. The main objective was to quantify harvesting effects on invertebrate assemblages across two contrasting habitats (soft- and hard-bottom), by comparing communities in marine protected areas (MPAs) with non-MPAs using 10 biological and ecological traits. Patterns of trait composition were compared with those of species composition by non-metric multidimensional scaling and permutational analysis of variance analyses. Traits most responsible for differences between MPAs and non-MPAs were determined using SIMPER analysis, and predictions on shellfishing effects were discussed. A total of 248 species were recorded in hard-bottom communities, mainly characterized by mobile epifauna living on corals, crawling, and possessing a shell (molluscs) or a cuticle (crabs and echinoderms). Soft-bottom habitats contained 166 species, dominated by burrowing and sedentary species, especially shelled (largely bivalves) and worm-like organisms. Clear differences in species and trait composition between MPA and non-MPAs were highlighted in both habitats. Harvesting activities have community-wide effects that change the functional composition of invertebrate assemblages, in particular in terms of living habits and mobility. The observed shifts in benthic communities can affect the functioning of tropical coastal ecosystems and need to be included in small-scale fisheries management in poorly known tropical environments.